Optimization of slant scanning in the systems of combined two-step location - Абдуллаев, Новруз Алмамед оглы; Асадов, Хикмет Гамид оглы (Eastern-European Journal of Enterprise Technologies, 2015)
Two structures of two-step location systems of terrestrial objects were highlighted in the paper. In the first structure, both location system units are terrestrial, the first determines one target coordinate, and the second - another. In the second structure, the second unit is mounted on the flying carrier. Carrier coordinates are determined by the first unit and target coordinates are determined by the scanner surveying of the object location. The scanner unit performs slant terrain scanning that dictates the need to optimize the slant scanning. A comparative analysis of the known energy-information optimization criterion and the proposed information-energy criterion was conducted. It is shown that the proposed criterion in some circumstances has a higher sensitivity than the information indicator. Optimization of the slant scanning of the terrestrial field was carried out according to the proposed criterion. Conditions for the target functional to achieve the minimum in solving the optimization problem by variational optimization at imposing limitations on the relative amount of information were found.